Cosmic rays from the nearby starburst galaxy NGC 253: the effect of a low-luminosity active galactic nucleus - Gutiérrez, Eduardo Mario (2020)
NGC 253 is a nearby starburst galaxy in the Sculptor group located at a distance of ∼3.5 Mpc that has been suggested by some authors as a potential site for cosmic ray acceleration up to ultrahigh energies. Its nuclear region is heavily obscured by gas and dust, which prevents establishing whether or not the galaxy harbours a supermassive black hole coexisting with the starburst. Some sources have been proposed in the literature as candidates for an active nucleus. In this work, we aim at determining the implications that the presence of a supermassive black hole at the nucleus of NGC 253 might have on cosmic ray acceleration. With this aim, we model the accretion flow on to the putative active nucleus, and we evaluate the feasibility of particle acceleration by the black hole dynamo mechanism. As a by-product, we explore the potential contribution from non-thermal particles in the accretion flow to the high-energy emission of the galaxy. We found that in the three most plausible nucleus candidates, the emission of the accretion flow would inhibit the black hole dynamo mechanism. To rule out completely the influence that a putative nucleus in NGC 253 might have in cosmic ray acceleration, a better clarification concerning the true nature of the nucleus is needed.